Social media and consumer behavior - Tuten, Tracy (Henry Stewart Talks, 2013)
Understand what is social media and the zones of social media, Social media definition, Zones of social media, Know consumer motives for using social media, Consumer behavior online, Motivations for consumers to use social media, Reflect on how consumers use social media, Social media participation, Social technographics, Understand the decision-making process and how social media can influence that process